# Subtract:

(i) -5y^{2} from y^{2}

(ii) 6xy from -12xy

(iii) (a – b) from (a + b)

(iv) a(b – 5) from b(5 – a)

(v) -m^{2} + 5mn from 4m^{2} – 3mn + 8

(vi) -x^{2} + 10x – 5 from 5x – 10

(vii) 5a^{2} – 7ab + 5b^{2} from 3ab – 2a^{2} – 2b^{2}

(viii) 4pq – 5q^{2} – 3p^{2} from 5p^{2} + 3q^{2} – pq

**Solution:**

Let us subtract the given algebraic expressions.

(i) - 5y^{2} from y^{2}

= y^{2} - (-5y^{2})

= y^{2} + 5y^{2}

= 6y^{2}

(ii) 6xy from -12xy

= -12xy - 6xy

= -18xy

(iii) (a - b) from (a + b)

= (a + b) - (a - b)

= a + b - a + b

= 2b

(iv) a(b - 5) from b(5 - a)

= b(5 - a) - a(b - 5)

= 5b - ab - ab +5a

= 5a + 5b - 2ab

(v) - m^{2} + 5mn from 4m^{2} - 3mn + 8

= 4m^{2} - 3mn + 8 - (-m^{2} + 5mn)

= 4m^{2} - 3mn + 8 + m^{2} - 5mn

= 5m^{2} - 8mn + 8

(vi) - x^{2} + 10x - 5 from 5x - 10

= 5x - 10 - (- x^{2} + 10x - 5)

= 5x - 10 + x^{2} - 10x + 5

= x^{2} - 5x - 5

(vii) 5a^{2} - 7ab + 5b^{2} from 3ab - 2a^{2} - 2b^{2}

= 3ab - 2a^{2} - 2b^{2} - (5a^{2} - 7ab + 5b^{2})

= 3ab - 2a^{2} - 2b^{2} - 5a^{2} + 7ab - 5b^{2}

= 10ab - 7a^{2} - 7b^{2}

(viii) 4pq - 5q^{2} - 3p^{2} from 5p^{2} + 3q^{2} - pq

= 5p^{2} + 3q^{2} - pq - (4pq - 5q^{2} - 3p^{2})

= 5p^{2} + 3q^{2} - pq - 4pq + 5q^{2} + 3p^{2}

= 8p^{2} + 8q^{2} - 5pq

**☛ Check: **NCERT Solutions for Class 7 Maths Chapter 12

**Video Solution:**

## Subtract: (i) - 5y² from y²^{ }(ii) 6xy from -12xy (iii) (a – b) from (a + b) (iv) a(b – 5) from b(5 – a) (v) -m² + 5mn from 4m² – 3mn + 8 (vi) -x² + 10x – 5 from 5x – 10 (vii) 5a² – 7ab + 5b² from 3ab – 2a² – 2b²(viii) 4pq – 5q² – 3p² from 5p² + 3q² – pq

Maths NCERT Solutions Class 7 Chapter 12 Exercise 12.2 Question 3

**Summary:**

On subtracting the expressions we get: (i) -5y^{2} from y^{2} = 6y^{2 }(ii) 6xy from -12xy = −18xy (iii) (a – b) from (a + b) = 2b (iv) a(b – 5) from b(5 – a) = 5a + 5b − 2ab (v) - m^{2} + 5mn from 4m^{2} – 3mn + 8 = 5m^{2} – 8mn + 8 (vi) -x^{2} + 10x – 5 from 5x – 10 = x^{2} – 5x – 5 (vii) 5a^{2} – 7ab + 5b^{2} from 3ab – 2a^{2} – 2b^{2} = 10ab – 7a^{2} – 7b^{2} (viii) 4pq – 5q^{2} – 3p^{2} from 5p^{2} + 3q^{2} – pq = 8p^{2} + 8q^{2} – 5pq

**☛ Related Questions:**

- A What Should Be Added To X2 Xy Y2 To Obtain 2x2 3xy B What Should Be Subtracted From 2a 8b 10 To Get 3a 7b 16
- What Should Be Taken Away From 3x2 4y2 5xy 20 To Obtain X2 Y2 6xy 20
- A From The Sum Of 3x Y 11 And Y 11 Subtract 3x Y 11 B From The Sum Of 4 3x And 5 4x 2x2 Subtract The Sum Of 3x2 5x And X2 2x 5
- Add I 3mn 5mn 8mn 4mn Ii T 8tz 3tz Z Z T Iii 7mn 5 12mn 2 9mn 8 2mn 3 Iv A B 3 B A 3 A B 3

visual curriculum